2013
DOI: 10.1186/bcr3441
|View full text |Cite|
|
Sign up to set email alerts
|

Cyclin D1 cooperates with p21 to regulate TGFβ-mediated breast cancer cell migration and tumor local invasion

Abstract: IntroductionDeregulation of the cell cycle machinery is often found in human cancers. Modulations in the cell cycle regulator function and expression result not only in proliferative advantages, but also lead to tumor progression and invasiveness of the cancer. In particular, cyclin D1 and p21 are often over-expressed in human cancers, correlating with high tumor grade, poor prognosis and increased metastasis. This prompted us to investigate the role of the cyclin D1/p21 signaling axis downstream of transformi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
64
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(69 citation statements)
references
References 75 publications
4
64
0
1
Order By: Relevance
“…Furthermore, our data confirmed that a significant reduction of CDK4, P70S6K, and Cyclin D1 with increased P53 in TRIM22 knockdown K562 cells (Figures C and D). CDK4, P70S6K, Cyclin D1, and P53 are pivotal regulators involved in cell cycle to affect tumor cell proliferation, and P53 is a well‐known anti‐oncogene (Skomedal et al, ; Jirawatnotai et al, ; Dai et al, ; Wang et al, ; Qiu et al, ). Above these results, TRIM22 deficiency inhibits cell proliferation via inducing cell cycle arrest by regulating cell cycle‐related proteins in CML cells.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, our data confirmed that a significant reduction of CDK4, P70S6K, and Cyclin D1 with increased P53 in TRIM22 knockdown K562 cells (Figures C and D). CDK4, P70S6K, Cyclin D1, and P53 are pivotal regulators involved in cell cycle to affect tumor cell proliferation, and P53 is a well‐known anti‐oncogene (Skomedal et al, ; Jirawatnotai et al, ; Dai et al, ; Wang et al, ; Qiu et al, ). Above these results, TRIM22 deficiency inhibits cell proliferation via inducing cell cycle arrest by regulating cell cycle‐related proteins in CML cells.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, c-Myb was found to bind to the Axin2 promoter directly, and thereby to induce Axin2 expression and enhance breast tumor progression. High expression of Cyclin D1 promotes local invasion and is associated with bone metastasis (41). Axin2 can fine-tune Wnt signaling and counteract excessive signaling as a Wnt feedback inhibitor, but, more importantly, Axin2 also acts as a chaperone for GSK3b and controls its subcellular location in human breast cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Although p21 has been known as the inhibitor of CDKs, the coexpression of cyclin D1 and p21 protein is required for the initial steps of tumor development. The overexpression of cyclin D1 and p21 are often reported in human cancers and is correlated with a high tumor grade and poor prognosis (Dai et al, 2013).…”
Section: Discussionmentioning
confidence: 99%